A computer tool for cardiovascular risk estimation according to Framingham and SCORE equations. Issue 2 (19th February 2012) - Ramírez‐Rodrigo, Jesús; Moreno‐Vázquez, José Antonio; Ruiz‐Villaverde, Alberto; Sánchez‐Caravaca, María Ángeles; Lopez de la Torre‐Casares, Martín; Villaverde‐Gutiérrez, Carmen
Abstract Background Currently, we have different scales to estimate the cardiovascular risk of one individual. The most commonly used in clinical practice are the Framingham method and the SCORE project. Both are based on mathematical models that take into account the presence and intensity of various risk factors for cardiovascular morbidity and mortality. Aims and objectives The aim of our study was to develop a measurement system that allows unifying criteria of both models. Thus, we will be able to estimate the cardiovascular risk globally in a cohort of patients instead of individually. Methods The study included a representative subgroup of 50 patients treated at in the Endocrinology Service of Virgen de las Nieves University Hospital, Granada, below 30 years or above 75 years. The equations used in the present study were in strict compliance with the original publications. The reliability and validity of results were tested, comparing them with results obtained using calculation programs developed, available on‐line. The degree of similarity was determined by means of the Dice index and the distance between our values and those of the other programs were compared by using the expression: Da–b = √Σ(a − b)2 Results The results of the present study demonstrated our application to be reliable and valid for cardiovascular risk assessment. Our observations also demonstrated differences in the criteria applied to create cardiovascular risk calculation tools. This may have repercussions on clinical decisions for some patients, suggesting a need to compare and standardize these criteria, ensuring that programs developed for this calculation correctly manage the different risk categories considered. Conclusion The present study validates a computer tool developed for the simultaneous calculation of cardiovascular disease probability by applying Framingham‐Anderson and Framingham‐Wilson methods, the Spanish adaptations of Regicor and Dorica, and the SCORE project.